(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article examines the evolution of genre preferences in the creative work of Dmitry Revyakin — a poet, composer, and the leader of the band Kalinov Most. The study analyzes the main stages of the artist’s development: from an early rock–folk synthesis to philosophical, mystical, and religious forms. Special attention is given to the interaction of genre models (folk rock, singer-songwriter tradition, spiritual poetry) and the individual authorial style.